A legal study on the abandonment of animal in Malaysia with regards to the Animal Act 1953 / Siti Safiah Rosli, Nur Aqilah Zainal Abidin and Asmaa Nadhirah Zanol Rashid - Rosli, Siti Safiah; Zainal Abidin, Nur Aqilah; Zanol Rashid, Asmaa Nadhirah (2014)
This research paper aims to address the issues of animal abandonment in Malaysia. Chapter 1 of this paper is the proposal of for this research. It is the preliminary steps before a research is conducted. The proposal contains the background of this research, problem statement, research questions, research objectives and research methodology. Second chapter of this research deals with introduction on abandonment supported by various sources and evidence from news, books and journal. It also contains the problems of animal abandonment and its consequences. The third chapter of this paper deals with the legislations in Malaysia. The first part of chapter three revolves on the Animal Act 1953. It also introduces the inadequacy of Animal Act 1953. We have included an analysis on the existing legislation in Malaysia with the Australian Companion Animals Act 1998. Chapter four of this research consists on the interview session done with the enforcement officers of Veterinary Services Department, Ministry of Agriculture and Agro-Based Industry Malaysia on issues regarding animal abandonment. Lastly, chapter five deals with the recommendation that we would propose to the authority in improving the animal welfare as well as curbing the animal abandonment problems in Malaysia.